Measurement of CKM element |V cb | from W boson decays at the future Higgs factories - Hao Liang; LingFeng Li; Yongfeng Zhu; Xiaoyan Shen; Manqi Ruan (Journal of High Energy Physics)
Abstract This study investigates the precision measurement of the CKM matrix element |V cb | through semileptonic WW events at future Higgs factories, i.e., FCC-ee, ILC, C3, and CEPC. We use full detector simulation to generate the WW → ℓνcb signal events and various backgrounds at s $$ \sqrt{s} $$ = 240 GeV with unpolarized beams. The relative statistical uncertainties of |V cb | are projected to be 0.91% for the muon channel and 1.2% for the electron channel, assuming a baseline integrated luminosity of 5 ab−1. The sensitivities at other Higgs factory scenarios are also projected. Possible contributors to systematic uncertainties are discussed, with the most prominent one being the systematics of flavor-tagging and mistagging rates. Combining with WW threshold runs, the relative systematic uncertainty can be further reduced.